Coumarins from Casimiroa edulis and their retinoic acid receptor agonist activity - Manami Haba; Naohito Abe; Ken-ichi Nakashima; Yuki Sakurai; Satoshi Okubo; Takao Yamaura; Makoto Inoue; Masayoshi Oyama (Natural Product Research, 2026)

A New Species of Sphaerospora Thélohan, 1892 (Myxozoa: Myxosporea: Bivalvulida) From the Japanese Rice Frog Fejervarya kawamurai: The First East Asian Record of Anuran-Parasitic Sphaerosporids - Ken Inoue; Kanto Nishikawa (Acta Parasitologica, 2026)

Monitoring the immune landscape against rabies in domestic dogs, Japan - Yuri Amemiya; Satoshi Inoue; Ken Maeda; Akira Nishizono; Yusuke Inoue; Naoto Ito; Hiroshi Nishiura (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Consensus Paper: Models of Cerebellar Functions - Shinji Kakei; Andreea C. Bostan; Timothy J. Ebner; Mohammad Amin Fakharian; Hiroaki Gomi; Xavier Guell; Marie Hemelt; Huu Hoang; Court Hull; Masato Inoue; Takahiro Ishikawa; Masashi Kameda; et al. (The Cerebellum, 2026)

Three-dimensional resistivity structure and its relationship to the rupture of the 1997 Kagoshima earthquake doublet (Mw 6.1 and 6.0), Japan - Keita Matsunaga; Koki Aizawa; Koichi Asamori; Hiroki Ogawa; Mitsuru Utsugi; Ryokei Yoshimura; Ken'ichi Yamazaki; Kazunari Uchida; Takeshi Matsushima; Tomohiro Inoue; Kohei Yonemori; Hiromichi Shigematsu (Tectonophysics, 2025)

Antioxidative activity of fractionated melanoidin-like product from molasses and its application in phytodesalination through oilseed rape - Ken-ichi Hatano; Ayu Ikeda; Naokazu Aoyagi; Yuuki Satoh; Saki Inoue (Environmental Science and Pollution Research, 2025)

Changes in the coastal environments and their impact on society in the Qaanaaq region, northwestern Greenland - Shin Sugiyama; Atsushi Yamaguchi; Tatsuya Watanabe; Yasumasa Tojo; Naotaka Hayashi; Jean-Baptiste Thiebot; Makoto Tomiyasu; Kohei Hasegawa; Yoko Mitani; Mayuko Otsuki; Yuta Sakuragi; Monica Ogawa; et al. (Polar Science, 2025)

Enhanced design of pCMViR-TSC plasmid vector for sustainably high cargo gene expression in mammalian cells - Masakiyo Sakaguchi; Rie Kinoshita; Nahoko Tomonobu; Yoshihiko Sakaguchi; Junichiro Futami; Akira Yamauchi; Hitoshi Murata; Ken-ichi Yamamoto; Tetta Takahashi; Yuma Gohara; Toshiki Ochi; Fan Jiang; et al. (In Vitro Cellular & Developmental Biology - Animal, 2024)
The first-generation pCMViR-TSC, implemented through the promoter sandwich rule, yields 10- to 100-fold higher gene expression than the standard plasmid used with the CMV (cytomegalovirus) or CAG promoter. However, the vector’s shortcomings limit its utility to transient expression only, as it is not suitable for establishing stable transformants in mammalian cells. To overcome this weakness, we here introduce the improved plasmid vector pSAKA-4B, derived from pCMViR-TSC as a second-generation chromosome-insertable vector. This vector facilitates the linear entry of the expression unit into the TTAA site of DNA universally with transposase assistance. The vector is helpful for the indefinite expression of our target gene. The new vector system is proven here to be efficient in establishing stable transformants with a high likelihood of positive clones that exhibit significantly elevated expression levels of the delivered foreign gene. This system, alongside the first-generation vector, is therefore instrumental for diverse basic research endeavors concerning genes, proteins, cells, and animals, and potentially for clinical applications such as gene therapy.

Kudoa tanakai n. sp. (Myxozoa: Myxosporea: Multivalvulida), a new kudoid species with spheroid myxospores from the scalpel sawtail (Actinopterygii: Prionurus scalparum) from western Japan - Ken Inoue; Akihiro Kasai; Ying-Chun Li; Jin-Yong Zhang; Hiroshi Sato (Systematic Parasitology, 2024)

The need for measures to prevent radiation exposure in Ukraine, taking both internal and external exposure into account - Ken Inoue; Noriyuki Kawano; Nariaki Fujimoto; Nobuo Takeichi; Masaharu Hoshi (Journal of Environmental Radioactivity, 2023)

Phylogenetic and population genetic analyses of plantago asiatica mosaic virus isolates reveal intraspecific diversification - Minako Furuya; Shino Tanai; Islam Hamim; Yuna Yamamoto; Haruki Abe; Kazuho Imai; Hiroki Saito; Kazuo Yamashita; Tamaki Uehara-Ichiki; Kaoru Hanada; Tatsuya Kon; Maki N. Inoue; et al. (Journal of General Plant Pathology, 2023)

Regulation of adipogenesis through retinoid X receptor and/or peroxisome proliferator-activated receptor by designed lignans based on natural products in 3T3–L1 cells - Ken-ichi Nakashima; Marina Okamura; Imari Matsumoto; Nanae Kameda; Tomoe Tsuboi; Eiji Yamaguchi; Akichika Itoh; Makoto Inoue (Journal of Natural Medicines, 2023)

Therapeutic angiogenesis for patients with no-option critical limb ischemia by adipose-derived regenerative cells: TACT-ADRC multicenter trial - Yuuki Shimizu; Kazuhisa Kondo; Ryo Hayashida; Ken-ichiro Sasaki; Masanori Ohtsuka; Yoshihiro Fukumoto; Shinichiro Takashima; Oto Inoue; Soichiro Usui; Masayuki Takamura; Masashi Sakuma; Teruo Inoue; et al. (Angiogenesis, 2022)

Descriptions of Three New Species and New Host or Distribution Records of Five Species of the Genus Kudoa (Myxozoa: Myxosporea: Multivalvulida) in Commercial Fishes Collected from South China Sea - Ying-Chun Li; Ken Inoue; Jin-Yong Zhang; Hiroshi Sato (Acta Parasitologica, 2022)

Two new ɑ-pyrone derivatives from the endophytic Diaporthe sp. ECN371 - Ken-ichi Nakashima; Yuka Higuchi; Junko Tomida; Yoshiaki Kawamura; Makoto Inoue (Journal of Natural Medicines, 2022)

Management of regional bone bank during declaration of a state of emergency concerning the COVID-19 in Japan - Kentaro Uchida; Manabu Mukai; Masayuki Miyagi; Kensuke Fukushima; Katsufumi Uchiyama; Akiko Nakayama; Mai Matsumoto; Naonobu Takahira; Ken Urabe; Masashi Takaso; Gen Inoue (Cell and Tissue Banking, 2021)

Aldolase C is a novel molecular marker for folliculo-stellate cells in rodent pituitary - Ken Fujiwara; Takehiro Tsukada; Kotaro Horiguchi; Yoko Fujiwara; Konomi Takemoto; Junko Nio-Kobayashi; Nobuhiko Ohno; Kinji Inoue (Cell and Tissue Research, 2020)

New Cerebello-Cortical Pathway Involved in Higher-Order Oculomotor Control - Xiaofeng Lu; Ken-ichi Inoue; Shogo Ohmae; Yusuke Uchida (The Cerebellum, 2020)

Correction to: Sesquiterpenes with new carbon skeletons from the basidiomycete Phlebia tremellosa - Ken-ichi Nakashima; Junko Tomida; Takao Hirai; Yoshiaki Kawamura; Makoto Inoue (Journal of Natural Medicines, 2020)
The article Sesquiterpenes with new carbon skeletons from the basidiomycete Phlebia tremellosa , written by Ken ichi Nakashima, Junko Tomida, Takao Hirai, Yoshiaki Kawamura and Makoto Inoue was originally published Online First without Open Access.

Correction to: Neuroprotective effect of naturally occurring RXR agonists isolated from Sophora tonkinensis Gagnep. on amyloid-β-induced cytotoxicity in PC12 cells - Wei Wang; Ken-ichi Nakashima; Takao Hirai; Makoto Inoue (Journal of Natural Medicines, 2019)

Sesquiterpenes with new carbon skeletons from the basidiomycete Phlebia tremellosa - Ken-ichi Nakashima; Junko Tomida; Takao Hirai; Yoshiaki Kawamura; Makoto Inoue (Journal of Natural Medicines, 2019)

Effects of Repeated Pulmonary Exposure to Carbon Nanotubes on Lung function - Michitaka Tanaka; Ken-ichiro Inoue; Akinori Shimada; Tatsuya Mimura; Hirohisa Takano (Toxicology and Environmental Health Sciences, 2019)

Anti-inflammatory effects of naturally occurring retinoid X receptor agonists isolated from Sophora tonkinensis Gagnep. via retinoid X receptor/liver X receptor heterodimers - Wei Wang; Ken-ichi Nakashima; Takao Hirai; Makoto Inoue (Journal of Natural Medicines, 2019)

Neuroprotective effect of naturally occurring RXR agonists isolated from Sophora tonkinensis Gagnep. on amyloid-β-induced cytotoxicity in PC12 cells - Wei Wang; Ken-ichi Nakashima; Takao Hirai; Makoto Inoue (Journal of Natural Medicines, 2019)

Nutrient deficiency promotes male-biased apparent sex ratios at the ramet level in the dioecious plant Myrica gale var. tomentosa in oligotrophic environments in bogs - Inoue Mizuki; Kiyoshi Ishida; Masaaki Chiwa; Yoshitoshi Uehara; Ken’ichi Shinozuka; Atsushi Kume (Journal of Plant Research, 2018)

Development of a new benzodiazepine hypnotics withdrawal symptom scale - Mina Kobayashi; Isa Okajima; Hajime Narisawa; Takashi Kikuchi; Kentaro Matsui; Ken Inada; Jun Ishigooka; Yuichi Inoue (Sleep and Biological Rhythms, 2018)

DNA hypermethylation enhanced telomerase reverse transcriptase expression in human-induced pluripotent stem cells - Ken Takasawa; Yoshikazu Arai; Mayu Yamazaki-Inoue; Masashi Toyoda; Hidenori Akutsu; Akihiro Umezawa; Koichiro Nishino (Human Cell, 2018)

Essential role of the PSI–LHCII supercomplex in photosystem acclimation to light and/or heat conditions by state transitions - Yoko Marutani; Yasuo Yamauchi; Mari Higashiyama; Akihito Miyoshi; Seiji Akimoto; Kanako Inoue; Ken-ichi Ikeda; Masaharu Mizutani; Yukihiro Sugimoto (Photosynthesis Research, 2017)

Pteleifolols A–E, acetophenone di-C-glycosides and a benzopyran dimer from the leaves of Melicope pteleifolia - Ken-ichi Nakashima; Naohito Abe; Fang-Rong Chang; Makoto Inoue; Masayoshi Oyama (Journal of Natural Medicines, 2017)

MCAM, as a novel receptor for S100A8/A9, mediates progression of malignant melanoma through prominent activation of NF-κB and ROS formation upon ligand binding - I. Made Winarsa Ruma; Endy Widya Putranto; Eisaku Kondo; Hitoshi Murata; Masami Watanabe; Peng Huang; Rie Kinoshita; Junichiro Futami; Yusuke Inoue; Akira Yamauchi; I. Wayan Sumardika; Chen Youyi; et al. (Clinical & Experimental Metastasis, 2016)

Atranorin and lecanoric acid antagonize TCDD-induced xenobiotic response element-driven activity, but not xenobiotic response element-independent activity - Ken-ichi Nakashima; Hiroki Tanabe; Yoshiaki Fujii-Kuriyama; Hidetoshi Hayashi; Makoto Inoue (Journal of Natural Medicines, 2016)

Investigation of Endogenous Compounds for Assessing the Drug Interactions in the Urinary Excretion Involving Multidrug and Toxin Extrusion Proteins - Koji Kato; Haruyuki Mori; Tomoko Kito; Miyu Yokochi; Sumito Ito; Katsuhisa Inoue; Atsushi Yonezawa; Toshiya Katsura; Yuji Kumagai; Hiroaki Yuasa; Yoshinori Moriyama; Ken-ichi Inui; et al. (Pharmaceutical Research, 2014)

Genetic and phenotypic characterization of a Japanese wild-derived DOB/Oda rat strain - Takashi Kuramoto; Satoko Inoue; Yuki Neoda; Ken-ichi Yamasaki; Ryoko Hashimoto; Tomoji Mashimo; Sen-ichi Oda; Tadao Serikawa (Mammalian Genome, 2013)

Phosphorylation of d-allose by hexokinase involved in regulation of OsABF1 expression for growth inhibition in Oryza sativa L. - Takeshi Fukumoto; Akihito Kano; Kouhei Ohtani; Megumi Inoue; Akihide Yoshihara; Ken Izumori; Shigeyuki Tajima; Yoshio Shigematsu; Keiji Tanaka; Takeo Ohkouchi; Yutaka Ishida; Yoko Nishizawa; et al. (Planta, 2013)

Compensatory Recovery of Blood Glucose Levels in KKAy Mice Fed a High-Fat Diet: Insulin-Sparing Effects of PACAP Overexpression in β Cells - Yusuke Sakurai; Hiroaki Inoue; Norihito Shintani; Akihiro Arimori; Ken-ichi Hamagami; Atsuko Hayata-Takano; Akemichi Baba; Hitoshi Hashimoto (Journal of Molecular Neuroscience, 2012)

Inhibitory effects of the transcription factor Ets-1 on the expression of type I collagen in TGF-β1-stimulated renal epithelial cells - Kazuhiro Okano; Asako Hibi; Tokiko Miyaoka; Tomoko Inoue; Himiko Sugimoto; Ken Tsuchiya; Takashi Akiba; Kosaku Nitta (Molecular and Cellular Biochemistry, 2012)

Biological control of apple crown gall by nonpathogenic Rhizobium vitis strain VAR03-1 - Akira Kawaguchi; Ken-ichi Kondo; Koji Inoue (Journal of General Plant Pathology, 2012)

Expression of the bacterial heavy metal transporter MerC fused with a plant SNARE, SYP121, in Arabidopsis thaliana increases cadmium accumulation and tolerance - Masako Kiyono; Yumiko Oka; Yuka Sone; Michitaka Tanaka; Ryosuke Nakamura; Masa H. Sato; Hidemitsu Pan-Hou; Kou Sakabe; Ken-ichiro Inoue (Planta, 2012)

Mg-chelatase H subunit affects ABA signaling in stomatal guard cells, but is not an ABA receptor in Arabidopsis thaliana - Tomo Tsuzuki; Koji Takahashi; Shin-ichiro Inoue; Yukiko Okigaki; Masakazu Tomiyama; Mohammad Anowar Hossain; Ken-ichiro Shimazaki; Yoshiyuki Murata; Toshinori Kinoshita (Journal of Plant Research, 2011)

Enhanced expression of human cDNA by phosphoglycerate kinase promoter-puromycin cassette in the mouse transthyretin locus - Zhenghua Li; Gang Zhao; Jingling Shen; Kimi Araki; Kyoko Haruna; Seiya Inoue; Jun Wang; Ken-ichi Yamamura (Transgenic Research, 2011)

Cerulein-Induced Acute Pancreatitis in PACAP Knockout Mice - Yusuke Sakurai; Norihito Shintani; Akihiro Arimori; Ken-ichi Hamagami; Naoko Higuchi; Hiroaki Inoue; Kazuya Ikeda; Atsuko Hayata; Hitoshi Hashimoto; Akemichi Baba (Journal of Molecular Neuroscience, 2011)

Nest intrusion and infanticidal attack on nestlings in great cormorants Phalacrocorax carbo: why do adults attack conspecific chicks? - Yukiko Inoue; Ken Yoda; Hidenori Fujii; Hirofumi Kuroki; Yasuaki Niizuma (Journal of Ethology, 2010)

Specific pathogen free conditions prevent transthyretin amyloidosis in mouse models - Seiya Inoue; Mika Ohta; Zhenghua Li; Gang Zhao; Yutaka Takaoka; Naomi Sakashita; Kazuhisa Miyakawa; Koji Takada; Hajime Tei; Misao Suzuki; Michio Masuoka; Yoshiyuki Sakaki; et al. (Transgenic Research, 2008)

Effects of naphthoquinone on airway responsiveness in the presence or absence of antigen in mice - Ken-ichiro Inoue; Hirohisa Takano; Takamichi Ichinose; Shigeo Tomura; Rie Yanagisawa; Miho Sakurai; Daigo Sumi; Arthur K. Cho; Kyoko Hiyoshi; Yoshito Kumagai (Archives of Toxicology, 2007)

A one-dimensional model for water quality simulation in medium- and small-sized rivers - Bui Quoc Lap; Ken Mori; Eiji Inoue (Paddy and Water Environment, 2007)

Identification of bovine QTL for growth and carcass traits in Japanese Black cattle by replication and identical-by-descent mapping - Akiko Takasuga; Toshio Watanabe; Yasushi Mizoguchi; Takashi Hirano; Naoya Ihara; Atsushi Takano; Kou Yokouchi; Akira Fujikawa; Kazuyoshi Chiba; Naohiko Kobayashi; Ken Tatsuda; Toshiaki Oe; et al. (Mammalian Genome, 2007)

Effects of organic chemicals derived from ambient particulate matter on lung inflammation related to lipopolysaccharide - Ken-ichiro Inoue; Hirohisa Takano; Rie Yanagisawa; Seishiro Hirano; Takahiro Kobayashi; Takamichi Ichinose; Toshikazu Yoshikawa (Archives of Toxicology, 2006)

Effects of nano particles on cytokine expression in murine lung in the absence or presence of allergen - Ken-ichiro Inoue; Hirohisa Takano; Rie Yanagisawa; Takamichi Ichinose; Miho Sakurai; Toshikazu Yoshikawa (Archives of Toxicology, 2006)

KDN (Deaminated neuraminic acid): Dreamful past and exciting future of the newest member of the sialic acid family - Sadako Inoue; Ken Kitajima (Glycoconjugate Journal, 2006)

The role of toll-like receptor 4 in airway inflammation induced by diesel exhaust particles - Ken-ichiro Inoue; Hirohisa Takano; Rie Yanagisawa; Seishiro Hirano; Takamichi Ichinose; Akinori Shimada; Toshikazu Yoshikawa (Archives of Toxicology, 2006)

Pulmonary exposure to diesel exhaust particles induce airway inflammation and cytokine expression in NC/Nga mice - Ken-ichiro Inoue; Hirohisa Takano; Rie Yanagisawa; Takamichi Ichinose; Akinori Shimada; Toshikazu Yoshikawa (Archives of Toxicology, 2006)

Pulmonary exposure to diesel exhaust particles induces airway inflammation and cytokine expression in NC/Nga mice - Ken-ichiro Inoue; Hirohisa Takano; Rie Yanagisawa; Takamichi Ichinose; Akinori Shimada; Toshikazu Yoshikawa (Archives of Toxicology, 2005)

Hybrid lethality of cultured cells of an interspecific F1 hybrid of Nicotiana gossei Domin and N. tabacum L. - Masanobu Mino; Yuko Misaka; Junko Ueda; Ken’ichi Ogawa; Masayoshi Inoue (Plant Cell Reports, 2005)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Effects of angiotensin-II receptor blocker candesartan cilexetil in rats with dilated cardiomyopathy - Ken Shirai; Kenichi Watanabe; Meilei Ma; Mir I I Wahed; Mikio Inoue; Yuki Saito; Palaniyandi Selvaraj Suresh; Takeshi Kashimura; Hitoshi Tachikawa; Makoto Kodama; Yoshifusa Aizawa (Molecular and Cellular Biochemistry, 2005)

Impact of aquatic plants on entrainment phenomena based on wind-induced flow in a closed density stratified water area - Akinori Ozaki; Ken Mori; Eiji Inoue; Tomokazu Haraguchi (Paddy and Water Environment, 2004)

Lung expression of cytochrome P450 1A1 as a possible biomarker of exposure to diesel exhaust particles - Hirohisa Takano; Rie Yanagisawa; Takamichi Ichinose; Kaori Sadakane; Ken-ichiro Inoue; Sei-ichi Yoshida; Ken Takeda; Shin Yoshino; Toshikazu Yoshikawa; Masatoshi Morita (Archives of Toxicology, 2002)

Wind Fields over Funka Bay and Their Effect on Water Circulation in the Bay - Jun Inoue; Masayuki Kawashima; Kay I. Ohshima; Yasushi Fujiyoshi; Ken-ichi Maruyama (Journal of Oceanography, 2000)

Evidence of pollen transfer efficiency as the natural selection factor favoring a large corolla of Campanula punctata pollinated by Bombus diversus - Shiro Kobayashi; Masahiro Kato; Ken Inoue (Oecologia, 1997)